The prognostic impact of the extent of ulceration in patients with clinical stage I–II melanoma: a multicentre study of the Italian Melanoma Intergroup (IMI). (15th June 2020) - Portelli, F.; Galli, F.; Cattaneo, L.; Cossa, M.; De Giorgi, V.; Forte, G.; Fraternali Orcioni, G.; Gianatti, A.; Indini, A.; Labianca, A.; Maurichi, A.; Merelli, B.; et al.
Summary: Background: The presence of ulceration has been recognized as an adverse prognostic factor in primary cutaneous melanoma (PCM). Objectives: To investigate whether the extent of ulceration (EoU) predicts relapse‐free survival (RFS) and overall survival (OS) in PCM. Materials and methods: We retrieved data for 477 patients with ulcerated PCM from databases of the Italian Melanoma Intergroup. Univariate and multivariable Cox proportional hazard models were used to assess the independent prognostic impact of EoU. Results: A significant interaction emerged between Breslow thickness (BT) and EoU, considering both RFS ( P < 0·0001) and OS ( P = 0·0006). At multivariable analysis, a significant negative impact of EoU on RFS [hazard ratio (HR) (1‐mm increase) 1·26, 95% confidence interval (CI) 1·08–1·48, P = 0·0047] and OS [HR (1‐mm increase) 1·25, 95% CI 1·05–1·48, P = 0·0120] was found in patients with BT ≤ 2 mm, after adjusting for BT, age, tumour‐infiltrating lymphocytes, sentinel lymph node status and mitotic rate. No impact of EoU was found in patients with 2·01–4 mm and > 4 mm BT. Conclusions: This study demonstrates that EoU has an independent prognostic impact in PCM and should be recorded as a required element in pathology reports. Abstract : What is already known about this topic? Ulceration is a well‐known prognostic factor in melanoma. There are conflicting results on the prognostic value of the extent of ulceration. What does this study add? The extent of ulceration is an independent prognostic factor in primary cutaneous melanoma with Breslow thickness (BT) ≤ 2 mm. The extent of ulceration should be incorporated into the pathology report as a required, core element. Patients with extensive ulceration with a BT ≤ 2 mm are at high risk of recurrence and should be included in prospective adjuvant trials. Linked Comment: Wilkinson and Gyorki. Br J Dermatol 2021; 184:192–193 .